Praktik Jual Beli Bahan Bangunan Dengan Sistem Pembayaran Tempo (Istijrar) Dalam Perspektif Ekonomi Islam - Rahmat; Musdalifah; Argarini, Galuh Mustika (Jurnal At-Tamwil: Kajian Ekonomi Syariah, 2023)
Qualitative research is the background design in this study. The subjects in the study were owners, employees and consumers of UD. Hamura Terang East Klampis district Klampis Bangakalan Regency. Data collection uses three types, namely; interviews, observation, and documentation. While the methods used to analyze data include; Reduction, Display, and Conclusion. The results of this study state that the sale and purchase of building materials with a tempo payment system (Istijrar) at UD. Hamura Terang Klampis Timur is a category of buying and selling that occurs between the shop and consumers in the process of ordering commodity goods made directly to the shop. The commodity ordered will be sent after the consumer has paid a down payment of 20% and both parties have agreed on the time of repayment. In the payment process that is done in tempo maximum time limit of one month will be given. The price offered has no difference between the purchase in cash or in tempo. The transaction is with a tempo payment system (Istijrar) carried out at the UD. Hamura Terang Klampis Timur is in accordance with the existing provisions in the Islamic Economic order and is a form of Ba'i Istijrar or Ba'i Bitsaman Ajil contract transactions.